Emergence of resistant variants detected by ultra‐deep sequencing after asunaprevir and daclatasvir combination therapy in patients infected with hepatitis C virus genotype 1. Issue 2 (19th June 2014) - Kosaka, K.; Imamura, M.; Hayes, C. N.; Abe, H.; Hiraga, N.; Yoshimi, S.; Murakami, E.; Kawaoka, T.; Tsuge, M.; Aikata, H.; Miki, D.; Ochi, H.; et al.
Summary Daclatasvir (DCV) and asunaprevir (ASV) are NS5A and NS3 protease‐targeted antivirals respectively, currently under development for the treatment of chronic hepatitis C virus (HCV) infection. We analysed the relationship between pre‐existing drug‐resistant variants and clinical outcome of the combination treatment with DCV and ASV. Ten patients with HCV genotype 1b were orally treated with a combination of ASV and DCV for 24 weeks. The frequencies of amino acid (aa) variants at NS3 aa positions 155, 156 and 168 and at NS5A aa31 and 93 before and after treatment were analysed by ultra‐deep sequencing. We established a minimum variant frequency threshold of 0.3% based on plasmid sequencing. Sustained virological response (SVR) was achieved in 8 out of 10 patients (80%), and relapse of HCV RNA after cessation of the treatment and viral breakthrough occurred in the other two patients. Pre‐existing DCV‐resistant variants (L31V/M and/or Y93H; 0.9–99.4%) were detected in three out of eight patients who achieved SVR. Pre‐existing DCV‐resistant variants were detected in a relapsed patient (L31M, Y93H) and in a patient with viral breakthrough (Y93H); however, no ASV‐resistant variants were detected. In these patients, HCV RNA rebounded with ASV‐ and DCV‐ double resistant variants (NS3 D168A/V plus NS5A L31M and Y93H). While pre‐existing DCV‐resistant variants might contribute to viral breakthrough in DCV and ASV combination therapy, the effectiveness of prediction of the outcome of therapy based on ultra‐deep sequence analysis of pre‐existing resistant variants appears limited.